Implementasi Kebijakan Peraturan Daerah Nomor 9 Tahun 2018 tentang Penyelenggaraan Reklame di Kabupaten Sukoharjo - Silvia Chindy Monica; Sapto Hermawan; Asianto Nugroho (Tamilis Synex: Multidimensional Collaboration, 2024)
The purpose of this research is to evaluate the implementation of Regional Regulation Policy Number 9 of 2018 concerning billboards in Sukoharjo Regency and to identify obstacles and efforts related to billboard management. This empirical study was conducted at the One-Stop Investment and Integrated Service Office (DPM-PTSP) and the Civil Service Police Unit (Satpol PP) in Sukoharjo Regency, using both primary and secondary data sources. Data were collected through interviews and literature reviews, with analysis employing the deductive syllogism technique, which involves reasoning from premises to conclusions. Findings indicate that Satpol PP has coordinated with agencies like BKD, PLN, and DPU, and has implemented educative and preventive measures by issuing warnings to billboard organizers. However, challenges include insufficient equipment, such as cranes, the need for better coordination with PLN for electrical issues, and difficulties in identifying billboard owners due to third-party involvement in the licensing process. Efforts to enhance policy effectiveness include acquiring additional equipment, improving inter-agency coordination, simplifying the licensing process, educating the public, enforcing laws consistently, and conducting periodic evaluations. These actions reflect a commitment to creating an orderly and safe environment.